2022
DOI: 10.3390/jcm11030531
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Flow Assessment in Doppler Ultrasonography in Risk Stratification of Patients with Internal Carotid Stenosis and Occlusion

Abstract: (1) Background: Alterations of blood flow volume in extracranial arteries may be related to the risk of occurrence of neurological symptoms. The aim of this study was the estimation of cerebral blood flow (CBF) in Doppler ultrasonography, as well as comparison of the flow volume in asymptomatic patients over 65 years old with ≥50%, and symptomatic patients with ≥70% internal carotid artery (ICA) stenosis, in order to assess whether the changes in the CBF correlates with the presence of neurological symptoms. (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The significant compensatory elevation of CBF is more frequently observed in asymptomatic patients suffering from severe ICA stenosis, which suggests its protective influence on developing ischaemic symptoms. The relative risk of observing the compensatory increased flow in extracranial arteries in asymptomatic patients is almost two times higher than in symptomatic ones [ 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The significant compensatory elevation of CBF is more frequently observed in asymptomatic patients suffering from severe ICA stenosis, which suggests its protective influence on developing ischaemic symptoms. The relative risk of observing the compensatory increased flow in extracranial arteries in asymptomatic patients is almost two times higher than in symptomatic ones [ 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the preliminary research our team identified a cut-off point in almost exactly one sigma from the mean. Not only did it allow us to identify the differences between asymptomatic and symptomatic patients but it also permitted a prediction of the postoperative increase in CBF in patients who undergo surgical treatment due to ICA stenosis [ 12 , 41 ]. Narrowing the confidence interval is acceptable when there are justified indications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study that used multimodal ultrasound to investigate plaque risk stratification in patients with asymptomatic carotid stenosis, plaque surface morphology, intraplaque neovascularization grades, and carotid stenosis degree were found to be risk factors for ischemic vascular events [ 22 ]. Also, a study using doppler ultrasonography to assess global cerebral inflow discovered that individuals with decreased cerebral blood flow were more likely to develop ischemia, providing a novel and simple way for detecting patients at risk of cerebral ischemia [ 23 ]. However, ultrasound is used primarily in assessing the echogenicity of plaques and has lower sensitivity for detecting plaque ulceration when compared to CT and MR angiography [ 6 ].…”
Section: Discussionmentioning
confidence: 99%